Calcium signalling in immune cells - Ng, S; Siaw Wei Ng (2011)
Inappropriate stimulation of mast cells can trigger allergies including asthma, allergic rhinitis and eczema which, combined, affect almost 30% of the population in western societies. Mast cell activation begins with aggregation of IgE receptors in response to antigen. This then triggers a series of reactions resulting in the tyrosine phosphorylation of Syk kinase, PKC activation and ultimately both degranulation and secretion of leukotrienes and cytokines. CRAC channels are expressed on mast cells, and are essential for IgE-mediated mast cell activation. Previous work in our laboratory has shown that local Ca2+ influx through CRAC channels activates Ca2+-dependent phopholipase A₂, ERK and 5-lipoxygenase, resulting in LTC₄ secretion from mast cells. Therefore, I have investigated how Ca2+ microdomains through CRAC channels are detected and how they trigger cellular responses. I find that phosphorylation of Syk following antigen stimulation is enhanced by Ca2+ influx through CRAC channels. I also show synergy between CRAC channels and antigen in activating Syk. These findings reveal a novel positive feedback step in mast cell activation, where local Ca2+ entry through CRAC channels activates Syk which, in turn, supports CRAC channels. Earlier work from our group has demonstrated that in RBL cells, Ca2+ influx through CRAC channels induces expression of the gene c-fos, an important regulator of pro-inflammatory gene expression. I have discovered that local Ca2+ entry is sensed by the non-receptor tyrosine kinase Syk, which accumulates at the cell periphery. Syk then signals to the nucleus through recruitment of the transcription factor STAT5. The results therefore identify Syk as a new link in excitation-transcription coupling, converting local Ca2+ influx into expression of genes that are essential for immune cell activation. Activation of G protein-coupled cysteinyl leukotriene type I receptors by the pro-inflammatory molecule LTC₄ is tightly linked to immune cell function and the receptor is an established therapeutic target for allergies including asthma. Desensitization of cysteinyl leukotriene type I receptors arises following protein kinase C-dependent phosphorylation of three serine residues in the receptor C-terminus. Here I show that abolishing leukotriene receptor desensitization suppresses agonist-driven gene expression. Physiological concentrations of LTC₄ led to repetitive cytoplasmic Ca2+ oscillations, which were accompanied by the opening of store-operated CRAC channels in the plasma membrane. Ca2+ microdomains near the open channels were relayed to the nucleus to increase expression of the transcription factor c-fos. In the absence of receptor desensitization, agonist-driven gene expression was suppressed. Mechanistically, stimulation of non-desensitizing receptors evoked prolonged Ca2+ release, which led to accelerated Ca2+-dependent inactivation of CRAC channels and a subsequent loss of excitation-transcription coupling. Rather than serving to turn off a biological response, the experiments show that reversible receptor desensitization is an ‘on’switch’, sustaining long-term signalling in the immune system.